CNEMALOBINI, UNA TRIBU DE CARABIDAE (COLEOPTERA) ENDEMICA DE AMERICA DEL SUR - Roig-Juñent, Sergio (Acta Entomológica Chilena, 2022)
Cnemalobus Guérin-Ménéville 1838, an endemic carabid beetle genus from Southern South America is a monophyletic group and ineludes twenty four species. Cnemalobus is classified as a distinct tribe, Cnemalobini, and preliminary analysis suggests a closest relationship with the Holartic tribe Zabrini and the tropical tribe Morionini (supertribe Pterostichitae). Zabrini-Cnemalobini stock is hypothesided to has arisen in the centra-west región of Pangaea, and the allopatric isolation of ancestral stocks in Cretaceous time might be former the tribes Zabrini and Cnemalobini.